Wireless sensor networks leveraging the virtual infrastructure. - Olariu, S. (IEEE Network : the magazine of global information exchange)
Overlaying a virtual infrastructure over a physical network is a time-honored strategy for conquering scale. We design a general-purpose virtual architecture for wireless sensor networks and show that it can be leveraged by a number of different protocols.